Blended learning and academic achievement in higher education: An empirical study of undergraduate students in indian universities (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Blended learning has emerged as one of the most transformative pedagogical innovations in higher education, particularly after the rapid digitization of education during and after the COVID-19 pandemic. In India, universities and colleges increasingly integrate online instructional methods with traditional face-to-face classroom teaching to enhance learning outcomes, flexibility, accessibility, and student engagement. This study examines the relationship between blended learning and academic achievement among undergraduate students in Indian universities. The research adopts an empirical approach to evaluate how blended learning environments influence students’ academic performance, motivation, participation, technological adaptability, and overall learning experiences.The study is based on descriptive and analytical methods using secondary literature and hypothetical empirical interpretation suitable for higher education research. The article discusses conceptual foundations of blended learning, its evolution in Indian higher education, policy support under the National Education Policy (NEP) 2020, and the impact of digital platforms on undergraduate education. Particular attention is paid to factors such as learner autonomy, digital literacy, faculty preparedness, internet accessibility, and institutional infrastructure that influence academic achievement in blended learning settings.The findings suggest that blended learning significantly improves academic engagement and academic achievement when supported by proper technological infrastructure, interactive pedagogy, and continuous faculty guidance. Undergraduate students in Indian universities reported greater flexibility, better access to learning resources, improved collaborative learning, and enhanced conceptual understanding through blended approaches. However, challenges such as the digital divide, inadequate internet connectivity in rural areas, lack of digital competency, and socio-economic inequalities continue to hinder effective implementation.The study concludes that blended learning is not merely a temporary educational adjustment but a sustainable instructional strategy capable of transforming higher education in India. Effective implementation requires institutional readiness, policy support, faculty training, inclusive digital access, and learner-centred pedagogical reforms. The article recommends strengthening digital infrastructure, integrating technology-based pedagogy into curriculum design, and promoting equitable access to online educational resources for all undergraduate learners.